Performance on the readiness of UNITEN instructors for blended learning - Chen S.D.; Ali N.B.; Hameed T.M.; Din N.M. (Blue Eyes Intelligence Engineering and Sciences Publication, 2023)
This paper presents a study on the readiness of Universiti Tenaga National (UNITEN) for Blended Learning (BL) from the perspectives of instructors motivation. The data in the study have been collected from 25 instructors who have been actively teaching in UNITEN. The results show that the instructors are generally motivated and ready for BL. The most motivating factor is providing flexible learning environment using ICT. The other factors surveyed include interest of student in using technology for learning, willingness of instructor for online discussion, effectiveness of online learning, enrichment of students experience via BL and improvement in student participation through online collaboration. This study is concluded with recommendations on the categories of instructor who may need more attention to further improve their readiness. BEIESP.